The complete chloroplast genome of the brown alga Saccharina sp. ye-B (Laminariaceae: Phaeophyceae) from Sakhalin, Russia - Li, Yan (Mitochondrial DNA B Resour, 2021)
The complete chloroplast genome sequence of Saccharina sp. ye-B was determined using Illumina sequencing data. The chloroplast genome of Saccharina sp. ye-B is 130,587 bp in length, containing 139 protein-coding genes (PCGs), 3 ribosomal RNAs (rRNAs), and 28 transfer RNAs (tRNAs) genes. The phylogenetic reconstruction based on the chloroplast genomes of 11 brown algae resolves Saccharina sp. ye-B in a fully supported clade with S. japonica. The determination of the chloroplast genome of Saccharina sp. ye-B will benefit future algal genetics, evolution, and systematic studies in the Laminariaceae.